Counter-current extraction : an introduction to the design and operation of counter-current extractors - Hartland, Stanley (Pergamon Press, 1970)
Counter-Current Extraction: An Introduction to the Design and Operation of Counter-Current Extractors provide useful conclusions and results pertaining to counter-current extraction. This book aims to present illustrations of the various mathematical techniques as tools as well as means to an end. Organized into eight chapters, this book begins with an overview of the various aspects of the transfer of a single solute between two immiscible phases in counter-current flow. This text then describes all possible factors and obtains their relationship to the extraction factor and number of stages.